UAV-based survey of ancient white marble quarries on Mt Pentelikon: successes and challenges of a lidar and photogrammetric survey in a high-relief environment - Pike, Scott; Kemp, Adelaide; Drazen, Cassie (Journal of Greek Archaeology, 2025)
Of the marble producing regions in the eastern Mediterranean, Mt Pentelikon was among the most exploited in antiquity. Large-scale ancient quarrying on Mt Pentelikon began in the 5th century BC with the construction of the Older Parthenon and continued throughout the Classical, Hellenistic, and Roman periods. The quarries have been the source for many monumental works of art and architecture of the ancient world, most notably, the monuments on the Athenian Acropolis, including the Parthenon. Extensive quarrying activity on Mt Pentelikon ended after the Roman/ Early Byzantine period and did not start up again until the mid-19th century AD when large-scale organized extraction activities resumed during the construction boom of the modern Greek state. Work further intensified following the Second World War. In 1974, a moratorium on all quarrying on the south slope was enacted to protect the ancient quarries as the resurgence of activity was leading to the destruction of ancient artifacts, quarries, slip-tracks, and roads.